Synthesis, photophysics and electrochemical study of tin macrocycles - Khene, Mielie Samson (Rhodes University, Faculty of Science, Department of Chemistry, 2008)
Three non-peripherally substituted tin(IV) macrocylic compounds, octahexylphthalocyaninato dichlorotin(IV) (35a), octahexyltetrabenzo-5,10,15-triazaporphyrinato dichlorotin(IV) (35b) and octadecylphthalocyaninato dichlorotin(IV) (35c) were synthesized and their photophysical and electrochemical behaviour studied. Complex (35b), containing a CH group in place of one of the aza nitrogen atom of the phthalocyanine core, shows a split Q band due to its lower symmetry. The triplet state quantum yields were found to be lower than would be expected on the basis of the heavy atom effect of tin as the central metal for phthalocyanine derivatives (35a and 35c). In contrast, (35b) shows a triplet quantum yield Î¦T = 0.78. The triplet state lifetimes were solvent dependent, and were higher in THF than in toluene. Cyclic voltammetry and spectroelectrochemistry of the complexes revealed only ring based redox processes. This thesis also reports on the microwave syntheses of tetrasulphonated tin phthalocyanine and tetrasulphonated tin Î±,Î²,Î³-tetrabenzcorrole. The latter was only formed at low ratios (< 1:8) of 4-sulfophthalic acid to urea. Both complexes are aggregated in aqueous media, but can be partly or fully disaggregated by the addition of Triton X-100. The SnTSTBC complex has lower triplet life times and yields, while binding constant and quenching (of bovine serum albumin) constant are lower for SnTSTBC, compared to SnTSPc. Finally Non-peripherally (Î±) tetra- (40) and octa-(38a) substituted dodecyl-mercapto tin(IV) phthalocyanines where synthesized and the electrochemical behavior studied. Cyclic voltammetry and spectroelectrochemistry show ring-based reductions for (38a) and (40); the former shows two ring oxidations, while the latter shows only one ring based oxidation. The adsorption kinetics of (38a) and (40) on a gold electrode have been investigated by electrochemical impedance spectroscopy (EIS). The equilibrium constant (K) for the adsorption and the Gibbs free energy Î”G(ads) of the self-assembled monolayer (SAMs) were evaluated based on the Frumkin isotherm. The interaction factor between adsorbate "“adsorbate molecules is also discussed.
Keywords: Electrochemistry; Photochemistry; Phthalocyanines; Macrocyclic compounds; Spectrum analysis